Status and potentials of the Philippine cassava industry - Bacusmo, José L. (International Center for Tropical Agriculture, 2001)
Cassava is planted each year in about 120,000 hectares of agricultural land in the Philippines, producing about 1.8 million tonnes of cassava roots. Principal products of the processing industry are food, dried chips and starch. As a traded commodity, however, cassava contributes only about 2% to gross value-adding in agriculture. The following factors favor the expansion of the industry: a) trends in associated commodities, b) dwindling prime agricultural land, c) expanding demand for cassava products, and d) availability of improved technologies. As a food crop, demand for cassava is increasing and this trend is expected to continue with the increase in population and improvements in techniques for transforming cassava roots into more stable, convenient and attractive products. Cassava has gained gradual acceptance as a high-energy component in commercial feed formulations. This is fueled by chronic shortages and the resulting high price of domestically produced maize. In specific locations, farmers now recognize that intercropping cassava with maize and given optimum care, this cropping system is economically comparable to two maize monocrops, and provides a more reliable income. The outlook for the cassava starch industry in the Philippines is rather bleak. Trade liberalization and the absence of real government assistance in improving productivity and efficiency are threatening the survival of this sector. The agricultural modernization program, which is supposed to cushion the impact of trade liberalization, virtually has had no funding during the first two years from its passage, and until now has not produced anything of practical significance. With the negative outlook for the Philippine sugar industry, cassava emerged as the most viable alternative source of raw material for production of alcohol for liquor. San Miguel Corporation has been investing heavily on plant construction and supply base development since 1995. The greatest challenge in the future will be to put in place a system that results in an adequate and stable year-round supply of cassava for the distillery. Strengthening the cassava industry in the Philippines requires strengthening the linkage between production and markets accompanied by improved access to credit, supportive government policies and appropriate technical support.